Distribusi Peserta Jaminan Kesehatan Nasional pada Fasilitas Kesehatan Tingkat Pertama di Kecamatan Gubeng, Surabaya - Aqmarina Adzkia Rahmani; Nuzulul Kusuma Putri (Universitas Airlangga, 2023)
Background: The amount of capitation received by primary healthcare facilities under Indonesia National Health Insurance is based on the number of participants registered in the facilities. The imbalance in the number of participants per primary healthcare facilities causes disparities in the distribution of its capitation funds. The uneven distribution of participants also causes the imbalance of health risks managed by the primary healthcare facilities. Objective: This study aims to describe the distribution of National Health Insurance participants at First Level Health Facilities in Gubeng District, Surabaya City based on the type of FKTP and the location of the health facility in the village. Method: This study analyzes the Indonesia National Health Insurance membership data for 2021 at the BPJS Kesehatan KCU Surabaya. The case study in Gubeng Subdistrict, Surabaya was chosen to illustrate how the distribution of participants in the primary healthcare facilities is in an area that has relatively no problems with geographic access or the availability of referral health facilities. Results: The number of private primary healthcare facilities (clinics and private medical practice) in Gubeng Subdistrict is higher than the government's primary healthcare facilities (Puskesmas, TNI/POLRI Clinics) but the largest ratio of participants is in government primary healthcare facilities. Kelurahan Mojo in Gubeng had the largest number of primary healthcare facilities, but the largest ratio of participants was in Kelurahan Airlangga. At least 43.7% of the primary healthcare facilities in Gubeng Subdistrict had a ratio of participants above the average ratio of participants per primary healthcare facilities in the sub-district. Conclusion: The distribution of JKN participants to primary healthcare facilities in Gubeng District is uneven.